Pd–Ni electrocatalysts for efficient ethanol oxidation reaction in alkaline electrolyte - Zhang, Zhiyong; Xin, Le; Sun, Kai; Li, Wenzhen (International journal of hydrogen energy, 2011)
Pd xNi y/C catalysts with high ethanol oxidation reaction (EOR) activity in alkaline solution have been prepared through a solution phase-based nanocapsule method. XRD and TEM show Pd xNi y nanoparticles with a small average diameter (2.4–3.2 nm) and narrow size distribution (1–6 nm) were homogeneously dispersed on carbon black XC-72 support. The EOR onset potential on Pd 4Ni 5/C (−801 mV vs. Hg/HgO) was observed shifted 180 mV more negative than that of Pd/C. Its exchange current density was 33 times higher than that of Pd/C (41.3 × 10 −7 A/cm 2 vs. 1.24 × 10 −7 A/cm 2). After a 10,000-s chronoamperometry test at −0.5 V ( vs Hg/HgO), the EOR mass activity of Pd 2Ni 3/C survived at 1.71 mA/mg, while that of Pd/C had dropped to 0, indicating Pd xNi y/C catalysts have a better ’detoxification’ ability for EOR than Pd/C. We propose that surface Ni could promote refreshing Pd active sites, thus enhancing the overall ethanol oxidation kinetics. The nanocapsule method is able to not only control over the diameter and size distribution of Pd–Ni particles, but also facilitate the formation of more efficient contacts between Pd and Ni on the catalyst surface, which is the key to improving the EOR activity. ► Uniform Pd–Ni nanoparticles (1–6 nm) were prepared via a solution phase-based method. ► The Pd–Ni/C shows higher ethanol oxidation reaction activity than Pd/C catalyst. ► The EOR enhancement is attributed to unique interactions between surface Pd and Ni.